Utility and cost analysis of cholesteatoma histopathologic evaluation. (9th July 2013) - Kircher, Matthew L.; Thottam, Prasad J.; Bojrab, Dennis I.; Babu, Seilesh C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the correlation between the surgeon's intraoperative findings and histopathologic diagnosis of cholesteatoma specimens and the associated health care cost in requesting pathologic evaluation. Study Design Retrospective chart analysis. Methods Chart data were collected at a tertiary neurotology referral center from patients undergoing tympanomastoidectomy for chronic otitis media, with specimens submitted for pathologic review between 2010 and 2011. Correlation between the surgeon's intraoperative findings and the pathologic diagnosis was evaluated using a kappa statistic. Cost analysis for pathologic consultation was also reviewed. Results A Cohen's kappa value of 0.93 (P < .01) was found between the surgeon's intraoperative findings and pathologic diagnosis. Using accepted kappa magnitude guidelines, there is perfect agreement between the surgeon's intraoperative findings and pathologic diagnosis of cholesteatoma after tympanomastoidectomy. The average cost for microscopic evaluation of cholesteatoma (current procedural terminology code 88304) as estimated per 2012 Medicare reimbursement rates is $61.95. Conclusions In the absence of concern for other pathology, intraoperative findings of cholesteatoma are adequate to confirm diagnosis in patients undergoing tympanomastoidectomy for chronic otitis media without the use of histopathology. The increased cost of routine cholesteatoma histopathologic evaluation should be considered in future health care cost‐containing measures, as clinical utility appears to be low. Level of Evidence 4. Laryngoscope, 124:538–540, 2014